Synthesis and Characterization of Some Anti-bacterial Active Transition Metal Complexes of N'-[2-(2-Phenyl hydrazinyl) Phenyl] Benzothiohydrazide - Naji, Shaymaa H; Musa, Falih H (Al-Nahrain Journal of Science, 2018)
The ligand N'-[2-(2-Phenyl hydrazinyl) Phenyl] benzothiohydrazide (L) has been prepared from the reaction of ortho amino hydrazo benzene with phenyl isothiocyanate in mole ratio (1:1) and characterized by elemental analysis (C,H,N), H1, 13C-NMR, IR and Uv-Vis Spectroscopic methods . The complexes of the bivalent ions (Co (II), Ni (II), Cu (II), Cd (II) and Hg (II)) have been prepared and characterized. The structural diagnosis were established by IR, Uv- Visible spectrum, conductivities, atomic absorption and magnetic susceptibility. Chloride ion content was also evaluated by (Mohr method) .The suggested geometry of the complexes were octahedral around the metal ion with the (N,N,S) ligand coordinated in tridentate mode. , Kf, max for the complexes were estimated too.  for Co- complex was calculated. In addition biological activity of the ligand and complexes against two selected types of bacteria were also examined. Some of the complexes exhibited a good anti bacterial activities -2